2011
DOI: 10.1016/j.fm.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric gas plasma disinfection of chicken meat and chicken skin contaminated with Listeria innocua

Abstract: 20Gas plasmas generated at atmospheric pressure and ambient temperatures offer a possible 21 decontamination method for poultry products. The efficacy of cold atmospheric gas plasmas 22 for decontaminating chicken skin and muscle inoculated with Listeria innocua was examined. 23Optimization of operating conditions for maximal bacterial inactivation was first achieved 24 using membrane filters on which L. innocua had been deposited. Higher values of AC 25 voltage, excitation frequency and the presence of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(118 citation statements)
references
References 30 publications
5
112
0
1
Order By: Relevance
“…The results suggest that the usage of argon and helium as a process gas may provide more efficient decontamination. Antimicrobial activity of cold plasma treatment on meat and meat products has been shown in various studies (Kim et al 2011;Moon et al 2009;Noriega et al 2011;Song et al 2009). Depending on the time of exposure, type of used gas, plasma sources or treated product, influence of cold plasma treatment on inactivation of microorganism is different.…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that the usage of argon and helium as a process gas may provide more efficient decontamination. Antimicrobial activity of cold plasma treatment on meat and meat products has been shown in various studies (Kim et al 2011;Moon et al 2009;Noriega et al 2011;Song et al 2009). Depending on the time of exposure, type of used gas, plasma sources or treated product, influence of cold plasma treatment on inactivation of microorganism is different.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the substrate itself can have a major impact on microbial survival. This was demonstrated by Noriega et al [25] who found that Listeria innocua survived the effects of plasma treatment better when applied to the skin of chicken than on chicken flesh. This was attributed to differences in surface topography; chicken skin is characterised by the existence of feather follicles inside which the bacteria are able to avoid the lethal effects of the plasma, whereas bacteria on the surface of the chicken flesh are more exposed to the chemical species present in the gas plasma.…”
Section: Introductionmentioning
confidence: 85%
“…Tissue surface irregularity enables contaminant bacteria to migrate from the surface into the tissue, protecting it from the biocidal effect of sterilization. [151] There are natural intercellular microholes on AM epithelial surface ( Figure 2A, B), which have been proven to allow gas transmission through dried and cryopreserved AM upon transplantation. [152,153] These microholes are impermeable to bacteria such as Escherichia coli, Pseudomonas, Klebsiella and Staphylococcus.…”
Section: Cap As a Potential Technique For Thin Tissue Sterilizationmentioning
confidence: 99%
“…[82] and mobility of plasma gas can allow for treatment of microspaces [123,155] . Recent studies reported CAP efficacy in reducing microbial contamination adhered to rough surfaces of chicken skin [151] , titanium implant surfaces [156] and root canals, especially in dry state conditions. [157] This supports the appropriate use of CAP for sterilization of dry AM with a comparably soft homogenous surface (Figure 2A, C).…”
Section: Cap As a Potential Technique For Thin Tissue Sterilizationmentioning
confidence: 99%